How common is isolated cardiac sarcoidosis? Extra-cardiac and cardiac findings on clinical examination and whole-body 18F–fluorodeoxyglucose positron emission tomography. (15th February 2018) - Juneau, Daniel; Nery, Pablo; Russo, Juan; de Kemp, Robert A.; Leung, Eugene; Beanlands, Rob S.B.; Birnie, David H.
Abstract: Background: Sarcoidosis is a systemic inflammatory disease which can involve nearly any organ. Clinically manifest cardiac involvement occurs in perhaps 5% of patients with sarcoidosis. The reported prevalence of isolated cardiac sarcoidosis (CS) varies widely with reported rates of 27–54%. The explanation for this variability is likely multi-factorial but perhaps mostly related to the diagnostic method(s) for assessing extra-cardiac involvement. The primary aim of this study was to assess the rate of isolated CS in a homogeneous, prospectively recruited cohort of patients with clinically manifest CS, using whole body FDG PET-CT imaging as a gold standard. A secondary aim was to describe the extent and distribution of extra-cardiac sarcoidosis at the time of first presentation of clinically manifest CS. Methods: Patients were prospectively recruited at the time of first presentation with cardiac symptoms. All patients underwent whole-body and cardiac 18 F–FDG PET-CT. All patients were examined for presence of skin sarcoidosis and were assessed by an ophthalmologist. Results: 31 patients were included (mean age 56 ± 8 years, 17 female, 100% Caucasian). Patients had limited extra-cardiac involvement (mean of 2.2 organs) however using the most precise definition, only 1/31 (3.2%) patients had isolated CS. There were marked differences in right ventricular (RV) and atrial involvement between patients presenting with CS as first presentation compared to patients presenting initially with extra-cardiac disease. Conclusions: Most patients had limited extra-cardiac involvement at the time of presentation of manifest CS however, isolated CS, using the proposed gold standard, was only observed in one patient.